Lifestyle advice, processes of care and glycaemic control amongst patients with type 2 diabetes in a South African primary care facility - Aswin Kalain; Olufemi B. Omole (AOSIS, 2020)
Background: The influence of processes of diabetes care on glycaemic control is understudied in primary health care (PHC). Aim: To explore the influence of lifestyle advice, drug regimen and other processes of care on glycaemic control. Setting: Johan Heyns Community Health Centre, Vanderbijlpark, South Africa. Methods: In a cross-sectional study involving 200 participants with type-2 diabetes, we collected information on sociodemography, comorbidity, processes of diabetes care, drug regimen and receipt of lifestyle advice. Anthropometric measures and glycosylated haemoglobin (HbA1c) were also determined. Results: Participants' mean age was 57.8 years and most were black people (88%), females (63%), overweight or obese (94.5%), had diabetes for 10 years (67.9%) and hypertension as comorbidity (98%). Most participants received lifestyle advice on one of diet, exercise and weight control (67%) and had their blood pressure (BP) checked (93%) in the preceding 12 months. However, 2% had any of HbA1c, weight, waist circumference or body mass index checked. Glycaemic control (HbA1c 7%) was achieved in only 24.5% of participants. Exclusive insulin or oral drug was prescribed in 5% and 62% of participants, respectively. Compared to insulin monotherapy, participants on combined metformin and insulin or metformin, sulphonylurea and insulin were less likely to have glycaemic control. Comorbid congestive cardiac failure (CCF) significantly increased the likelihood of glycaemic control. Conclusion: There is substantial shortcomings in the implementation of key processes of diabetes care and glycaemic control. Strategies are needed to prompt and compel healthcare providers to implement evidence-based diabetes guidelines during clinic visits in South African PHC.